Characterization of Anaphylatoxin Receptor Expression and C3a/C5a Functions in Anaphylatoxin Receptor Reporter Mice. (25th July 2020) - Laumonnier, Yves; Karsten, Christian M.; Köhl, Gabriele; Köhl, Jörg
Abstract: The anaphylatoxins (AT) C3a and C5a are effector molecules of C3 and C5 exerting multiple biologic functions through binding and activation of their cognate G protein−coupled receptors. C3a interacts with the C3a receptor (C3aR), whereas C5a and its primary degradation product C5a‐desArg engage C5aR1 and C5aR2. In the past, analysis of AT expression has been hampered by cross reaction of antibodies designed to recognize the different AT receptors. Furthermore, assessment of effects mediated by cell‐specific activation has been difficult. Here, floxed AT receptor reporter mice are described as tools to monitor AT receptor expression in cells and tissues and to study the functions of C3a and C5a by cell‐specific deletion of their cognate AT receptors. © 2020 The Authors. Basic Protocol 1 : Genotyping of floxed GFP‐C5aR1 knockin mice Support Protocol 1 : Genotyping of LysMcre‐C5ar1 ‐/‐ mice Basic Protocol 2 : Genotyping of floxed tdTomato‐C3aR and ‐tdTomato‐C5aR2 knockin mice Support Protocol 2 : Preparation of genomic DNA Basic Protocol 3 : Determination of C5aR1, C5aR2, and C3aR expression using floxed AT receptor reporter mice Support Protocol 3 : Determination of C3aR expression using a C3aR‐specific antibody Support Protocol 4 : Determination of C5aR1, C5aR2, and C3aR mRNA expression in floxed GFP‐C5aR1, floxed tdTomato‐C5aR2 or ‐tdTomato C3aR positive cells Basic Protocol 4 : Analysis of C5aR1‐driven ERK1/2 phosphorylation in GFP‐C5aR1 + cells Basic Protocol 5 : Assessment of C3aR functions in cells obtained from floxed tdTomato‐C3aR knockin mice‐ Determination of C3aR internalization Alternate Protocol : C3a‐induced increase in intracellular Ca 2+ Basic Protocol 6 : C5aR2‐driven IFN‐γ production from NK cells Support Protocol 5 : Isolation of splenic NK cells by FACS